New OCR letter addresses pregnancy discrimination. (10th March 2023) - Lyerly, Eric
Abstract : There has been a recent trend at the federal level to strengthen protections for pregnant women. In January 2023, U.S. Congress passed a spending package that included two pieces of legislation concerning pregnant workers and new mothers. The Pregnant Workers Fairness Act requires employers to provide reasonable accommodations to employees affected by pregnancy, child birth, or related conditions. The Providing Urgent Maternal Protections (PUMP) for Nursing Mothers Act provides protections for new mothers who need to pump breastmilk for a nursing child.